Hypothyroidism and sinus dysfunction associated with lithium-paliperidone combination therapy for bipolar disorder with psychotic symptoms: a case report - Wei, Wenjian; Yang, Yonglan; Wang, Haifeng; Yang, Yunbin; Liu, Jizhou; Li, Jinfeng (Frontiers in Psychiatry, 2024)
Background and aim Lithium is considered to be the first-line treatment for bipolar disorder, and paliperidone was approved for the treatment of schizophrenia and acute bipolar manic/mixed episodes. However, both agents have been associated with thyroid dysfunction and cardiovascular adverse effects like subclinical hypothyroidism, bradycardia, and sinus arrest, even at therapeutic doses. Case presentation Here, we reported a case of a 17-year-old Han Chinese female who developed symptomatic hypothyroidism, sinus bradycardia, and sinus arrest while being treated with lithium and paliperidone for bipolar disorder with psychotic features including auditory hallucinations. Her workup suggested that these adverse effects might be related to the combined lithium and paliperidone treatment, although other causes could not be ruled out. After discontinuing both medications, her thyroid function and heart rhythm normalized over 20 days. Conclusion To our knowledge, hypothyroidism, sinus bradycardia, and sinus arrest associated with the combined use of lithium and paliperidone had not been reported previously. Further research is warranted to elucidate the potential risks and benefits of this combination therapy for bipolar disorder with psychotic symptoms.